Seminar on Strengthening Effective Communication Competence for Religious Extension Workers at the Office of Religious Affairs - Abdul Hamid Bashori; Nur Imamah; Nur Hotimah; Darus Salam; Rofiki Rofiki; Ummu Dhafaratul Ummah (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2026)
Religious extension workers face challenges in delivering da'wah effectively, persuasively, and adaptively, resulting in messages that are often unclear, less courteous, and less relevant. This community service aims to enhance the communication competence of religious extension workers, making them more effective, empathetic, persuasive, and targeted. The methods employed include Participatory Action Research (PAR), material presentation, interactive discussions, Q&A sessions, and case studies, supported by facilities such as halls, projectors, screens, sound systems, training modules, notebooks, stationery, banners, certificates, refreshments, and seminar media. The participants are active functional and non-functional religious extension workers. The results indicate a significant improvement in communication understanding and skills, the ability to apply effective communication principles, interpersonal techniques, and adaptive da'wah strategies; practical simulations strengthened empathetic and persuasive abilities and expanded collaboration networks. In conclusion, the program successfully enhanced the competence and effectiveness of da'wah. Its significance demonstrates the contribution of higher education institutions to the development of religious human resources and the improvement of da'wah service quality.